(untitled) (Bangladesh Journal of Medical Science, 2025)
Objectives Combined usage of e-cigarettes (ECs) and conventional cigarettes (CCs) may result in prolonged use of both products. The objective of this study is to explore dual EC and CC users’ attempts, barriers, and reasons to quit. Materials and methods Twenty-seven dual users were recruited through snowball sampling, and data were collected via online focus group discussions using a validated open-ended interview guide. Results and discussion Participants provided contradictory responses, with some indicating attempts to quit but relapsing for a variety of reasons, while others reported making no attempt to quit. Barriers to quitting included social influences and EC dependence, while fear of health consequences, extrinsic motivation, financial cost, and intrinsic motivation emerged as sub-themes under reasons to quit. Utilising several types of nicotine have resulted in complicated patterns of transition and poly-use among various groups, which do not always result in smoking cessation behaviours, notably among dual users. Conclusion The current study provides novel insights regarding dual users in Malaysia, for targeted preventive, health promotion, and smoking cessation initiatives, as well as legislative recommendations for EC regulation in Malaysia. Bangladesh Journal of Medical Science Vol. 24 No. 02 April’25 Page : 560-568